HUBUNGAN SEJUMLAH KARAKTERISTIK PETANI METE DENGAN PENGETAHUAN MEREKA DALAM USAHATANI METE DI KABUPATEN BOMBANA, SULAWESI TENGGARA - Syafruddin Syafruddin; Amri Jahi; Richard W.E. Lumintang (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
The objectives of this study were: (1) To determine the distribution of cashew farmer in a number characteristics, (2) To assess the farmer’s knowledge in cashew farming and, (3) To determine the relationship of the cashew’s farmer characteristics and their knowledge in cashew farming. Ninetyone cashew farmers were interviewed in this study. Data were collected in July to September 2005. Data were analyzed by Kendall W Concordance procedure. The results of the study were as follows: The mean of the farmer‘s age was 41, the farmer’s formal education was secondary school, the farmer’s experience in cashew farming was 14 years, their motivations were high, their income was Rp. 5.4 million rupiahs per year, their farm size was 3.3 ha, their cashew trees was 467, their family size was 4 persons, their media consumtion was high, their cashew production was 2.9 ton per year, their contact with extension agent was good, and they did not have any prior training. The mean score of the farmers knowledge was 75.58. Knowledge that the farmers need were: (1) Agriculture technology, (2) Labour aspect, (3) Integrating cashew farm and livestock, and (4) Capital formation. There were high correlations between the farmer’s characteristics and the farmer’s knowledge in cashew’s farming.